A STUDY OF GLUCOSE-6-PHOSPHATE DEHYDROGENASEDEFICIENCY AMONG CHILDREN ATTENDING THE EMERGENCY HOSPITAL IN ZAKHO CITY-KURDISTAN REGION, IRAQ - Armishty, Farhad S. (Science Journal of University of Zakho, 2023)
Background: G6PD deficiency, which affects 400 million individuals globally, is an X-linked hereditary enzymopathy that causes acute hemolysis after exposure to specific oxidative agents such as fava beans, more than 37 drugs, and infections viral or bacterial. Neonatal jaundice worsened by kernicterus is one of the condition’s significant consequences. It can be prevented by avoiding the oxidative factors that cause a hemolytic episode alongside neonatal screening programs for early detection of afflicted individuals. Objectives: This research aimed at investigating the variability in clinical and biochemical manifestations among children with G6PDD. This is the first study to be carried out in the Zakho area. Methods: A cross-sectional study was used, recruiting 112 children attending Zakho Emergency Hospital from January 2022 to April 2023. Laboratory aids involved in obtaining CBC, liver enzyme activities, and blood grouping were all investigated. The IBM SPSS 26 program was used to analyze the obtained data. Results: There was no statistically significant difference between male and female patients in terms of age, time of admission, hemoglobin level, WBC count, and liver enzymes. The majority of cases who visited Zakho Emergency Hospital within 72 hours of exposure to the triggering agent were males (67.9%), with the most common clinical features being jaundice, dark urine, and abdominal pain. Conclusion: In this study, the three main symptoms in G6PD deficient patients with acute hemolysis were pallor, jaundice, and black urine. These signs appeared several hours or even days after consuming fava beans. The primary clinical symptoms and the patient’s gender, family history, or prior newborn jaundice were not related, according to our research.